Implementation and testing of the OPT Model as a teaching strategy in an undergraduate psychiatric nursing course...Outcome-Present State-Test - Bland AR; Rossen EK; Bartlett R; Kautz DD; Carnevale T; Benfield S (Nursing Education Perspectives (National League for Nursing))
Teaching undergraduate nursing students to think critically and reason clinically is a challenge for nurse educators, yet these skills are essential for the professional nurse. The Outcome-Present State-Test (OPT) Model of Reflective Clinical Reasoning (Pesut & Herman, 1999 ) provides a framework for teaching clinical reasoning skills to nursing students. This article describes how the model can be used in clinical teaching of undergraduate students in psychiatric and mental health settings and presents some findings from an evaluation of the model. Strategies employed in the model implementation are described, along with the benefits and limitations of this teaching method in a psychiatric clinical setting.